The hawk of the castle : a story of medieval falconry - Smith, Danna (Candlewick Press, 2017)
"Join a young girl and her father, the falconer at a medieval castle, as they experience the joys of taking a goshawk out for a training flight. The girl leads readers through all the preparations and equipment needed for the flight -- from falconer's glove to the hawk's hood and bells -- culminating in a dramatic demonstration of the hawk's hunting skills." -- From dust jacket.